ETIOLOGY, TREATMENT AND PREVENTION OF STOMACH CANCER - Alimov N (Journals Park Publishing, 2023)
Stomach cancer, a disease characterized by abnormal growth of cells in the stomach. The incidence of stomach cancer has decreased dramatically since the early 20th century in countries where refrigeration has replaced other methods of food preservation such as salting, smoking, and pickling. Stomach cancer rates remain high in countries where these processes are still used extensively. Worldwide it was the fifth most-common cancer in the 21st century.
Keywords: stomach, tissue, cancer, helicobacter pylori.